Optimalisasi Kinerja Saluran Drainase Studi Kasus Daerah Kelurahan Petisah Hulu, Medan Melalui Evaluasi Teknis - Rumilla Harahap; Seny Climenty Siagian; Edwart Samuel Gaby Siahaan; Rizky Simanjuntak; Wisnu Prayogo (JURNAL TECNOSCIENZA, 2026)
This study aims to assess the effectiveness of the drainage system in the urban area of Petisah Hulu Village in reducing the risk of flooding caused by high rainfall and rapid land use changes. Hydrological analysis was conducted using the Log Pearson Type III distribution to calculate the design rainfall, while the existing channel capacity was analyzed using the rational method. Based on the technical evaluation in the Final Report of the Medan Urban Drainage Plan (MUDP) Open Channel Inventory, the results of the study indicate a very high level of flood vulnerability. It was found that 58.4% of the total channel length did not meet the safety threshold criteria (freeboard < 30 cm) for the design flood discharge. The accumulation of surface runoff and domestic waste caused excess capacity of 41.6% at critical points, especially on Jalan Gajah Mada and Jalan S. Parman which flow into the Babura River. This decline in performance was significantly influenced by inadequate measurements.